PENY AJIAN AKTIVITAS CORPORATE SOCIAL RESPONSIBILITY (CSR) DALAM LAPORAN KEUANGAN - Warno, Warno (Sekolah Tinggi Ilmu Ekonomi Semarang, 2011)
The existence  of the concept  of CSR requires  companies  to have a broader  view is that companies   also  have  responsibilities    towards   other  parties   such  as  employees,   suppliers, consumers,  local communities,  society  at large, governments,   and groups  - other groups.  11 In this case,  if the previous footing   limited  liability  company  only at the financial   side only (single bottom  line),  now  known  as  the concept  of'triple    bottom  line',  namely  that  the  responsibility rests on three  basic  companies,  namely: financial,   social  and environmental   or also known  as 3P                                         (profit,                                         people,                                          planet). CSR  report  is a part  that  can  not  separate   the  components   of financial   statements. Where  in Indonesia   the components   complete financial   statements   based  on SFAS  1 (revised 2009)   consists   of  statements    of  financial    position    of   the   end   of   the  period,    reporting comprehensive   income,  changes  in equity, statement  of changes  in financial  position,  statement of financial   position   of  the  beginning   of  the period   and  notes  to financial   statements.   CSR reports separatelyfrom    the components  of financial  statements